The Relationship Between Social Support and the Incidence of Postpartum Depression among Primiparous Mothers - Herlina Grenanda; Istri Yuliani; Atik Ba'diah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Postpartum depression is a mental health disorder commonly experienced by women after the childbirth process, especially in primiparous mothers who are adjusting to their new role as a mother. Various factors can influence the occurrence of postpartum depression, including social support that encompasses support from a husband, parents, in-laws, and siblings. A lack of social support has the potential to increase the risk of psychological disorders in postpartum mothers, making it important to examine the relationship between social support and the incidence of postpartum depression. This research method uses a quantitative approach with a correlational analytical design. The sample consisted of 72 primiparous postpartum mothers registered at two Primary Clinics in the city of Samarinda. The sampling technique used was total sampling. Data collection was carried out cross-sectionally using the PSSQ and EPDS questionnaire instruments. Data analysis was conducted using the Chi-square test and ordinal logistic regression. The majority of respondents were aged 20-35 years (94.4%), had a secondary level education (40.3%), were unemployed (58.3%), had a family income above the regional minimum wage (62.5%), and had planned pregnancies (84.7%). The most frequently found postpartum depression level was in the mild category (38.9%). There was a significant relationship between social support from husbands (p=0.000), parents (p=0.012), in-laws (p=0.001), and siblings (p=0.002) with the occurrence of postpartum depression. Multivariate analysis showed that support from husbands was the most influential factor on postpartum depression (p=0.000), with a 2.031 times higher likelihood in mothers who received low support from their husbands. There is a significant relationship between family social support and the incidence of postpartum depression in primiparous mothers. Support from the husband is a key factor influencing the level of postpartum depression. Therefore, active involvement of the husband and family is very important in providing emotional, informational, and instrumental support to reduce the risk of postpartum depression.